Discursive enactment of power in Iranian high school EFL classrooms - Abdullah, Faiz Sathi; Hosseini, Kobra (Penerbit Universiti Kebangsaan Malaysia, 2012)
Teachers’ dominance in teaching environments has been criticized as an oppressive educational practice by critical theories of education. While critical pedagogy that espouses a problem-posing model of education has sought to promote a more equitable and dialogical teacher-student partnership and to transform the oppressive conditions of the ESL/EFL classroom, the claimed potential of the approach has had only limited success in practice. Drawing upon Fairclough’s approach to critical discourse analysis to make for a principled analysis of EFL classroom practice, this study investigated the discoursal features of unequal power relations in Iranian high school EFL classes. The data was collected via observation of two classrooms, one located in an urban area and the other in a semi-urban area of Iran. The analysis of the observation data, which included transcripts of classroom lessons as well as field notes, indicated that teachers played a disproportionately dominant role to the extent that the students were kept apparently passive and powerless via a range of discursive strategies including maximizing teacher-controlled talking time, turn-taking, topic control, modes of meaning-construction, and elicitation strategies. The findings of this study are expected to provide critical and emancipatory insights into ESL/EFL classroom practice and contribute to the transformation of its status quo.